1991
DOI: 10.1111/j.1365-2265.1991.tb03510.x
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine pretreatment modifies the growth hormone secretory pattern induced by shortterm continuous GRF infusion in normal man

Abstract: These data concord with our previous demonstration that clonidine disrupts the hypothalamic-somatotroph rhythm by inhibiting the hypothalamic release of somatostatin. Given that clonidine pretreatment induced a more physiological episodic pattern of GRF-induced GH release, the possibility of combining clonidine and GRF therapy for short stature in children is envisaged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…The data obtained in this study agree with previous findings of our group, demonstrating that the administra tion of CLO cojointly with GRF results in a synergistic stimulation of GH release in humans [8][9][10], dogs [11], and rats [13,14], Lanzi et al [15] recently confirmed our 555 results in rats. The potentiating effect of CLO on the GH response to GRF is more clearly seen when the somatostatinergic input to the pituitary is physiologically [8.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The data obtained in this study agree with previous findings of our group, demonstrating that the administra tion of CLO cojointly with GRF results in a synergistic stimulation of GH release in humans [8][9][10], dogs [11], and rats [13,14], Lanzi et al [15] recently confirmed our 555 results in rats. The potentiating effect of CLO on the GH response to GRF is more clearly seen when the somatostatinergic input to the pituitary is physiologically [8.…”
Section: Discussionsupporting
confidence: 83%
“…Initial data in rats suggested that this effect was dependent on the stimulation by CLO of hypothalamic GH-releasing hormone (GH-RH) release [3][4][5][6][7], Yet a wealth of other evidence indicated that in GH control. CLO might act mainly by inhibiting the hypotha- lamic secretion of somatostatin (SS), at least in humans [8][9][10], dogs [II], and rabbits [ 12]. Hence it appeared that, depending on the species, different mechanisms might be responsible for the GH-releasing effect of ctyadrenoceptor agonism.…”
Section: Introductionmentioning
confidence: 99%
“…30 for review], and although evidence obtained in experiments with rats suggests for CLO an action mediated via GHRH release [19][20][21][22], the possibility has to be considered that it may also act via inhibition of somatostatin release [II, 23,24], In this vein, recent studies have shown that CLO increases the GH release to GHRH both in obese children [31] and in normal men [32], This effect appears to be dependent on a decreased somatostatinergic input to the pituitary, re sulting as a consequence of a 2-adrenergic agonism. In the present study we did not measure the effect on GH re lease of CLO alone; however, it seems unlikely that the 4-fold increase in the GH response to GHRH following CLO was due to the drug-induced stimulation of endo genous GHRH release.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many recent data indicate that the aging-suppressor gene Klotho is a direct regulator of GH secretion [35]. However, we still think that the CLO+GHRH test is a clear reproducible and safe test for analyzing possible states of GH-deficiency and its causes, even in adulthood [36].…”
Section: Discussionmentioning
confidence: 99%